Debit Kid / Amizatul Hawariah Awang ... [et al.] - Awang, Amizatul Hawariah; Khairul Anwar, Muhammad Adib; Bakri, Nurul Fatin Najwa; Mohd Kamarul Ariffin, Aida Karmila (Universiti Teknologi MARA, Kedah, 2023)
Currently, people are still unaware of the state of their finances. A lot of them are still lacking in financial planning. This is due to the community’s lack of knowledge in the field of finance, as well as the disclosure of the necessity of financial planning. As a result, it is important to educate everyone, particularly young people such as students, on the necessity of financial planning. As an outcome, the Debit Kid product can assist students in better budgeting their money. Debit Kid is a student-only debit card. It can help kids get basic cashless knowledge. Other than that, it helps students save for the future. Hopefully, this Debit Kid will help people realize the necessity of financial planning.